2016
DOI: 10.1021/acs.nanolett.5b04838
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium Dichalcogenides: Layered Semiconductors with Two Vertical Orientations

Abstract: The rhenium and technetium diselenides and disulfides are van der Waals layered semiconductors in some respects similar to more well-known transition metal dichalcogenides (TMD) such as molybdenum sulfide. However, their symmetry is lower, consisting only of an inversion center, so that turning a layer upside-down (that is, applying a C2 rotation about an in-plane axis) is not a symmetry operation, but reverses the sign of the angle between the two nonequivalent in-plane crystallographic axes. A given layer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 43 publications
5
113
0
2
Order By: Relevance
“…Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodssupporting
confidence: 82%
“…Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodssupporting
confidence: 82%
“…L. Hart et al [15] also found similar phenomenon that the crystallographic b-axis of ReS2 flakes frequently formed the longer edge of cleaved crystals, clearly indicating larger appearance probability for b-axis than a-axis. This study is in good agreement with our experiment results.…”
Section: Resultsmentioning
confidence: 65%
“…[16,25,61] Owing to its unusual atomic structure and assymetric crystal growth, ReS2 exhibits different fundamental properties from other TMDs. Here below we have reviewed such properties.…”
Section: Fundamental Propertiesmentioning
confidence: 99%
“…This distortion in crystal structure renders weak coupling between interlayers which can result in the bulk ReS2 behaving like electronically 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 and vibrationally decoupled monolayers. [16,20,64] This is a significant advantage over other TMDs which undergo a transition from indirect to direct bandgap semiconductor when reduced from bulk to monolayer. The resilient bandgap with no direct-indirect transition offers remarkable possibilities to produce relatively large-area ReS2 of a single molecular layer thickness.…”
Section: Band Structure and Electronic Transportmentioning
confidence: 99%
See 1 more Smart Citation